Pineapple weevil extract (Ananas Comosus L. Merr) inhibits S.mutans in child dental caries: Ekstrak bonggol nanas (Ananas Comosus L. Merr) menghambat S.mutans pada karies gigi anak - Putu Yetty Nugraha; Eko Sri Yuni Astuti; Ni Made Shinta (Makassar Dental Journal, 2021)
Caries occurs due to the presence of pathogenic microorganisms such as Streptococcus mutans bacteria. One way to prevent caries is to inhibit the S.mutans bacteria. This study used the dilution method to determine the inhibition and killing power of pineapple (Ananas comosus L. Merr) weevil extract against S.mutans bacteria. The extract was obtained by maceration me-thod and made with concentrations of 25%, 50%, 75% and 100%. The results were extract with a maximum concentration of 50% could inhibit bacterial growth, at a concentration of 75% and 100% showed no bacteria growing on the media. The nor-mality test using Shapiro-Wilk, explained that data were normally distributed; the homogeneity test using the Levene test, ex-plained the data were homogeneous. One-way Anova was used to determine the differences between treatment groups and the value of ρ (Sig.) < 0.05 was obtained, which means that there is a significant difference and is continued with test least significant difference (LSD) to find out the difference in each concentration. The pineapple weevil extract have the inhibition and killing power to inhibit and kill bacteria S.mutans.